Mastoid and Opisthion-Bimastoid Triangles for Sex Determination in a Brazilian Sample - de Castro,Silvana Regina Prado Penteado (Sociedad Chilena de Anatomía, 2021)
SUMMARY: Human identification involving mutilation, advanced decomposition, and skeletonized materials is a challenge for professionals in forensic medicine and dentistry. This study was aimed at a morphometric analysis of the mastoid and bimastoid triangles to determine sex in a Brazilian population. The sample included 80 human skulls (34 females and 46 males; age: 18 to 60 years) from individuals with death certificates. Linear measurements (mm) of the mastoid process - right (n=3) and left (n=3) - and the opisthion- bimastoid (n=3) triangles were taken (digital caliper) by two previously trained researchers. Three cranial points - asterion, porion and process - were determined for the right and left mastoid triangle and three others - (1) opisthion and (2) right and (3) left mastoid - for the bimastoid triangle. Heron’s formula was used to calculate the area of the triangles assessed. Data were submitted to the Shapiro- Wilk normality test, followed by the unpaired Student's t test or the Mann-Whitney U test, depending on the data distribution verified in the normality test (GraphPad Prism 5.01; p<0.05). The ROC curve was used to measure the accuracy of the variables toward sex determination. The opisthion-bimastoid triangle showed high accuracy and significant differences in all the variables assessed and thus was considered a potential element for sex determination in the Brazilian population assessed.